2021
DOI: 10.1590/s1984-29612021097
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of Anaplasma marginale infecting dairy cattle in northeastern Brazil

Abstract: Anaplasma marginale is an obligate intracellular Gram-negative bacterium found in ruminants’ erythrocytes and is the etiological agent of bovine anaplasmosis. The bacterium’s genetic diversity has been characterized based on sequences of major surface proteins (MSPs), such as MSP1α. The aim of the present study was to investigate the genetic diversity of A. marginale in cattle in the state of Maranhão, northeastern Brazil. To this end, 343 blood samples were harvested and subjected to iELISA assays using the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…According to sex, prevalence was similar in female cattle (67.7%) than in male cattle (64.8%); therefore, no statistically significant differences were found ( Table 1 ). In a study under similar feeding conditions, the prevalence of A. marginale in cows was 59.5%, which was lower than the values found in this study [ 27 ]. These results differ with the study by Sisson et al [ 10 ], which mentions that males are more likely to be infected by A. marginale or A. centrale , due to the significant suppressive effect of testosterone on immune function in a variety of mammal species including cattle [ 28 ].…”
Section: Resultscontrasting
confidence: 86%
“…According to sex, prevalence was similar in female cattle (67.7%) than in male cattle (64.8%); therefore, no statistically significant differences were found ( Table 1 ). In a study under similar feeding conditions, the prevalence of A. marginale in cows was 59.5%, which was lower than the values found in this study [ 27 ]. These results differ with the study by Sisson et al [ 10 ], which mentions that males are more likely to be infected by A. marginale or A. centrale , due to the significant suppressive effect of testosterone on immune function in a variety of mammal species including cattle [ 28 ].…”
Section: Resultscontrasting
confidence: 86%
“…These results are consistent with previous results for strains found mainly in Brazil ( 19 , 20 , 38 ), Argentina ( 18 ) and Colombia ( 39 ). Other genotypes frequently observed in our work were G and H. Studies carried out in Brazil (São Paulo and Maranhão) reported that genotype H was the most frequently found in beef and dairy cattle ( 21 , 22 ). However, the genetic diversity of circulating strains in the equatorial zone, comprising the countries of Ecuador, Mexico, Cuba, and subtropical countries such as South Africa and the USA, are different, with G and C being the main genotypes ( 15 , 27 , 40 ).…”
Section: Discussionsupporting
confidence: 60%